Children on demand the ethics of defying nature - Frame, T. R. (Thomas R.), 1962- (UNSW Press, 2008)
"This is a book that starts of by acknowledging the pain of infertility for many people and then examines the options for conceiving that have developed so rapidly since Louise Brown the first 'test tube baby' was born 30 years ago. Tom Frame argues that ethics, law and community desires haven't been able to keep up with technological advancement, and that this is a problem. He starts by looking at adoption, and includes details about his own experience as an adoptee. He writes about sperm and egg donors, asking whether it's fair that they be allowed to remain anonymous; he writes about IVF and surrogacy and finishes by writing about cases where women have asked to use the dead husbands' stored sperm to become preganant. He looks at science, religion, philosophy, ethics but his starting point is always 'what's best for the child'. His view that the ideal family is a mother, a father and a child will create some controversy."--Provided by publisher.